Dual ligand immunoliposomes for drug delivery to the brain - Joana A. Loureiro (2015)
Drug delivery systems that can reach brain areas affected by amyloid deposits are still underdeveloped. We propose pegylated liposomes functionalized with two antibodies, the anti-transferrin receptor monoclonal antibody (0X26MAb) and the anti-amyloid beta peptide antibody (19B8MAb), as nanocarriers of drugs for Alzheimer's disease therapy. Two distinct conjugation methods are investigated. In one formulation, the OX26MAb is conjugated to the tip of polyethylene glycol molecules through the maleimide group and the 19B8MAb is bound through the streptavidin biotin complex. In the second system the conjugation reagents are swapped between the antibodies. Fluorescence spectroscopy experiments on porcine brain capillary endothelial cells show that the cellular uptake of the immunoliposomes is substantially more efficient if OX26MAb antibody is conjugated through the streptavidin biotin complex instead of the maleimide group. The ability of the immunoliposomes to cross the blood brain barrier was established by in vivo studies in wild type rats. Our results demonstrate the importance of the conjugation method used to bind the antibody that targets the blood brain barrier to immunoliposomes for efficient drug delivery to the brain.